A study on plasma Testosterone levels in Abudefduf vaigiensis at the Northeastern Persian Gulf - Zahra Soltanzadeh (Frontiers in Marine Science, 2015)
Although sex steroids play an important role in many physiological processes including reproduction in vertebrates there is a few information about the effects of these hormones on the reproduction of fishes, specially the coral-reef ones in literature. Evaluation of the fluctuations in these hormones is of the great importance in the reproductive studies. In the present research, we monitored monthly changes of the plasma levels of testosterone during the gonadal development for 120 Abudefduf vaigiensis specimens, collected randomly by the angling from a reef habitat at coastal waters of the eastern Qeshm Island, the northeastern Persian Gulf, through the Enzyme-linked immune-sorbent assay (ELISA) technique. The results exhibit the significant changes in the measured values of testosterone due to the role of these hormones in gonadal development during the vitellogenesis in six months of a year (October to March 2013). Thus, the mean value of the testosterone evaluated in the case of 47 female and 34 male specimens presents a significant reduction during winter compared to that of measured in autumn. The average measured testosterone were increased during the summer and reached to its maximum value in August in the case of both sexes.